Pengembangan Sistem Informasi Monitoring Kinerja Guru dan Siswa Menggunakan Metode Agile - Benni Dolles Pardosi; Elliana Gautama; Agnes Novita Ida Safitri; Mochamad Isnin Faried (STMIK Banjarbaru, 2025)
This study aims to develop a web-based monitoring information system for teachers and students using the Agile methodology. The system integrates the Google Classroom API to monitor teacher performance and student learning progress in real time. Unlike previous studies that focused only on academic data management, this research applies Agile stages—product backlog, sprint planning, execution, and review—in an iterative process involving teachers and students. The system was tested at Tunas Gading School, Jakarta, featuring key functions such as a teacher performance dashboard, student progress tracking, and automated task notifications. Results from User Acceptance Testing (UAT) show that 90% of teachers found the system helpful in monitoring student progress, while 85% of students benefited from task notifications. The system effectively improves learning monitoring efficiency and provides an innovative approach to automated academic monitoring integrated with online learning platforms.Keywords: Information System; Agile; Google Classroom; Academic Monitoring; Online Learning AbstrakPenelitian ini bertujuan mengembangkan sistem informasi monitoring kinerja guru dan siswa berbasis web menggunakan metode Agile. Sistem ini mengintegrasikan Google Classroom API untuk memantau kinerja guru dan perkembangan belajar siswa secara real-time. Berbeda dari penelitian sebelumnya yang hanya mengelola data akademik, pendekatan Agile diterapkan melalui tahapan product backlog, sprint planning, execution, dan review secara iteratif melibatkan guru dan siswa. Uji coba di Sekolah Tunas Gading Jakarta menampilkan fitur utama seperti dashboard kinerja guru, pemantauan progres siswa, dan notifikasi tugas otomatis. Hasil User Acceptance Testing (UAT) menunjukkan 90% guru menyatakan sistem membantu pemantauan siswa dan 85% siswa merasa terbantu dengan notifikasi tugas. Sistem ini meningkatkan efisiensi pemantauan pembelajaran serta menghadirkan inovasi dalam otomatisasi monitoring akademik terintegrasi dengan platform pembelajaran daring.